Floral biodiversity and geology of the Talcher Basin, Orissa, India during the Permian–Triassic interval. (8th June 2012) - Goswami, Shreerup; Singh, Kamal Jeet
<x xml:space="preserve">Abstract</x> The review paper provides an updated account of the previous and recently published records concerning the palaeobiology and the geology of the Talcher Basin of Orissa State, India. We conclude that fossil floral species in this basin originated in the earliest Permian Talchir Formation and evolved and diversified through the Karharbari Fm., Barakar Fm., Barren Measures Fm. and the uppermost Kamthi Fm. (Late Permian–Triassic). The megaflora and the palynology of the different formations of the basin are also discussed briefly. The geological setting of the basin along with the status of different formations (especially the Kamthi Formation) has been redefined. The post‐Barakar Fm. rocks, earlier retained in the Raniganj/Kamthi, Panchet and Mahadeva formations in this basin, have been critically assessed and redefined as the Lower and Upper Kamthi formations of Late Permian and Triassic ages, respectively. Accordingly, the geological map of the basin has been modified. Permian deposits (particularly the Barakar and the lower Kamthi formations) not only have the best preserved flora but also possess the highest diversity, whereas the upper Kamthi Triassic sediments have a meagre number of taxa. The plant diversity of the basin has been discussed in detail to interpret the development of the flora, evolutionary trends and palaeoenvironments of the basin. The patchy Gangamopteris vegetation of the Talchir glacial phase has ultimately evolved and diversified through time (Karharbari Fm. to Lower Kamthi Fm.) and gave rise to the thick dense swampy forests consisting of large Glossopteris trees and other shade‐loving under‐storied pteridophytes. Several groups of plants including spores and pollen have disappeared in a ladder pattern during the Permian–Triassic interval (Lower Kamthi–Upper Kamthi Fm.) and, similarly, in steps, many new fore‐runners appeared in the Upper Kamthi Formation. Records of marine acritarchs and ichnofossils in this basin at various Permian–Triassic levels demonstrate that there were marine influences. These features suggest a paralic (coastal marine to deltaic) mode of origin of the coal beds and associated sediments in the basin. The present study also advocates the continued survival of plants, rather than a mass extinction near the vicinity of the Permian–Triassic (P–T) boundary in this basin. Copyright © 2012 John Wiley & Sons, Ltd.